Entegre Bir Yazılım Çözümü ile Endüstriyel Ortamlarda Enerji Verimliliğinin Artırılması ve Gerçek Zamanlı İzleme: NIGHTWATCH - Selçuk, Kenan; Nikbay, Kader; Bilgin, Turgay Tugay (Kirklareli University, 2023)
Küresel olarak, ısınma, aydınlatma, ulaşım ve çeşitli cihazlar için yakıt temini gibi faktörler nedeniyle enerjiye olan talep artmaya devam etmektedir. Enerjinin böylesine büyük önem kazandığı bir bağlamda, enerji verimliliğinin sağlanması, enerji üretimi, iletimi ve tüketimiyle ilgili faaliyetleri kapsayan kapsamlı bir yaklaşım gerektirmiştir. Enerji alanındaki olumlu ya da olumsuz gelişmeler, sürdürülebilir kalkınmanın odak noktalarını oluşturan hem insani hem de çevresel faktörleri önemli ölçüde etkilemektedir. Sunulan çalışma, endüstriyel ortamlarda çalışmakta ve enerji analizörleri ile arayüz oluşturarak enerji tüketimi, anlık akım ve voltaj gibi verileri toplayıp analiz etmektedir. Bu girişim, fabrika tesislerinde enerjiyle ilgili operasyonlara gerçek zamanlı görünürlük sağlamayı amaçlamaktadır. Buna ek olarak, yazılımın yetenekleri geriye dönük veri analizine kadar uzanmakta ve gelecekteki tahminler için bilinçli içgörüler sağlamaktadır. Ayrıca, analizörlerden gelen enerji tüketimi verilerinin Üretim Yürütme Sistemine (MES) entegrasyonu, iş bazında enerji takibini kolaylaştırır. Yazılımın gösterge paneli bileşeni, kullanıcılara izlenen enerji parametreleri için özelleştirilmiş eşik değerleri belirleme yetkisi verir. Bu eşikler aşıldığında veya değerler beklenen seviyelerden saptığında, yazılım e-posta ve diğer iletişim kanalları aracılığıyla uyarıları ve bildirimleri tetikleyerek ilgili bilgilerin zamanında yayılmasını sağlar.

Globally, the demand for energy continues to escalate due to factors such as heating, lighting, transportation, and fuel supply for various devices. In a context where energy has garnered such paramount importance, achieving energy efficiency has necessitated a comprehensive approach encompassing activities related to energy generation, transmission, and consumption. Any positive or negative developments in the realm of energy significantly impact both human and environmental factors, which constitute the focal points of sustainable development. The presented study, operates within industrial settings and interfaces with energy analyzers, collecting and analyzing data such as energy consumption, instantaneous current, and voltage. This initiative seeks to provide real-time visibility into energy-related operations on factory premises. Additionally, the software's capabilities extend to retrospective data analysis, enabling informed insights for future extrapolations. Furthermore, the integration of energy consumption data from the analyzers into the Manufacturing Execution System (MES) facilitates energy tracking on a per-job basis. The software's dashboard component empowers users to establish customized threshold values for monitored energy parameters. When these thresholds are exceeded or when values deviate from expected levels, the software triggers alerts and notifications via email and other communication channels, ensuring timely dissemination of pertinent information. Consequently, the software allows businesses to evaluate unit costs associated with specific job orders. Additionally, the study aims to establish a correlation between energy consumption data at the job-order level and machine-level energy consumption. This correlation could foster the augmentation of efficient energy utilization, thereby enhancing competitiveness and overall efficacy.
Enhancing Energy Efficiency and Real-time Monitoring in Industrial Environments through an Integrated Software Solution: NIGHTWATCH
Keywords: Electronics; Sensors and Digital Hardware (Other); Elektronik; Sensörler ve Dijital Donanım (Diğer)